Wake up and open your eyes eaudiobook - Chapman, Clay (Blackstone Publishing, 2025)
From Vulture's "master of horror" Clay McLeod Chapman, a relentless and emotionally charged social horror novel about a family on the run from a demonic possession epidemic that spreads through media, for fans of The Last of Us and Where Evil Lurks Noah Fairchild has been losing his formerly polite Southern parents to far-right cable news for years, so when his mother leaves him a voicemail warning him that the "Great Reckoning" is here, he assumes it's related to one of the many conspiracy theories she believes in. But when his own phone calls go unanswered, Noah makes the long drive from Brooklyn to Richmond, Virginia. There, he discovers his childhood home in shambles, a fridge full of spoiled food, and his parents locked in a terrifying trance-like state in front of the TV. Panicked, Noah attempts to snap them out of it and get medical help. Then Noah's mother brutally attacks him. But Noah isn't the only person to be attacked by a loved one. Families across the country are tearing each other apart—literally—as people succumb to a form of possession that gets worse the more time they spend watching particular channels, using certain apps, or visiting certain websites. In Noah's Richmond-based family, only he and his young nephew Marcus are unaffected. Together, they must race back to the safe haven of Brooklyn—but can they make it before they fall prey to the violent hordes? This ambitious, searing novel from "one of horror's modern masters" holds a mirror to our divided nation, and will shake listeners to the core.